(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe the knowledge and practice on COVID-19 vaccine post-vaccination response and identify some factors related to parents’ knowledge and practice about COVID-19 vaccine postvaccination response at Quang Trung Secondary School, Vinh City in 2022. Subjects and research methods: A cross-sectional descriptive study with an analysis of 351 parents whose children at Quang Trung Secondary School have been vaccinated against COVID-19 since May. 2/2021-5/2021. Results: 49% of the respondents had good knowledge of the COVID-19 vaccine post-vaccination response. The rate of the study subjects who recognized common signs of reaction after vaccination with the COVID-19 vaccine was a low-grade fever of ≤ 38.5ºC, accounting for 83.5%. The percentage of study subjects who recognized abnormal signs after vaccination against COVID-19 was a very high fever of ≥ 40ºC; chest tightness, trouble breathing; convulsions had the same rate, respectively 78.6%; 73.8% and 72.9%; signs of generalized swelling had the lowest rate (51.9%). The rate of research participants who practiced monitoring for 30 minutes at the vaccination site and practiced monitoring for at least 24 hours at home was 95.4%. The sign of reactions after vaccination was a general condition (69.8%) and the least was rash (31.3%). Some factors such as education level, occupation, and information sources are related to the knowledge and practice of research subjects on response to COVID-19 vaccination. Conclusion: 49% of the respondents had good knowledge of the COVID-19 vaccine post-vaccination response. 60.4% of study subjects had good practice in response to COVID-19 vaccination. There is a relationship between education level, occupation, sources of information, knowledge, and practice of research subjects in response to COVID-19 vaccination.